Development of a concept-based postgraduate course: scholarship - Crous, Lizelle (My University, 2020)
There is an urgent need to introduce Advanced Practice Nursing (APN) in South Africa to deliver specialist healthcare services in this rapidly evolving healthcare landscape. Recent amendments to the nursing regulations require these nursing specialists to be prepared at a postgraduate diploma level. While specialisation categories for nursing practice do exist, there is no nursing specialist register, and thus for many of the nurses trained to work in these areas, there has not been a clear career pathway available. It is imperative that postgraduate diploma curricula for APN programmes are developed that produce nurses who engage scholarship within their practice. The purpose of the study was to develop an evidence-based postgraduate scholarship course which would contribute 30 credits towards a postgraduate diploma in an APN programme. There is a lack of clarity globally on the roles and attributes of an APN. It was necessary in this study to gain a clear picture of the APN’s role within the South African context, in order to develop a relevant scholarship programme which will produce an APN with appropriate competencies. A Design and Development Research (DDR) was implemented to guide the development of the programme. The five phases of DDR were: Phase 1) a scoping review which explored the characteristics of the APN from an international perspective; Phase 2) a Rank Order Scale (ROS) identified the desired characteristics of APN within the South African context and, where consensus was not achieved, a nominal group discussion sought clarification; Phase 3) the prototype of the scholarship for APN course was developed, applying educational theories related to conceptual learning and concept-based curriculum; Phase 4) Formative evaluation of the quality of the course in scholarship for APN was achieved through a workshop method with internal stakeholders; and Phase 5) the course scholarship in APN was validated by external educational experts using a review process. The product of the DDR is a 30 credit course in scholarship which will form part of a postgraduate diploma in APN that is contextually relevant to the South African healthcare landscape, produces the desired qualities of an APN as clarified through the initial phases of the study and which is both internally and externally validated. The study is limited by the delayed promulgation of the governing regulations that will determine the implementation and approval of the programme. At the time the study was conducted, the regulations were still open for comment which limited the opportunity to engage the broader stakeholder community and to summatively evaluate the programme through student participation. Recommendations for further research are to involve more v stakeholders in the evaluation of the course once implemented to determine if the programme objectives are met.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020